Highly efficient walking perovskite solar cells based on thermomechanical polymer films. Issue 45 (8th November 2019) - Qi, Jiabin; Li, Linpeng; Xiong, Hao; Wang, Aurelia Chi; Hou, Chengyi; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi
Abstract : Inspired by heliotropism in nature, a passive walking perovskite solar cell is constructed as a prototype actuator with an advanced structure. Abstract : Considering the trends towards miniaturization and automation of electronics, increasing attention should be given to self-actuating microenergy technologies. In particular, it is important for these systems to simultaneously possess simple structure, self-powered energy supply, and high power density. Using a facile and ultrafast fabrication approach, a highly efficient walking perovskite solar cell is constructed as a prototype actuator with a straightforward design but advanced functions. The device demonstrates a high walking speed of 10 mm min −1, excellent mechanical strength (the ability to lift an object 15 times its own weight), and high photoelectric efficiency, achieving a power conversion efficiency of 17.75% as a low-temperature flexible solar cell. The dynamic output of the device during passive heliotropic walking is also evaluated. The maximum output power of the device reaches 215 W m −2 . This device shows promise for use as a mobile energy source in various technological applications including microsensors, micropumps, and microrobots.